Three Solutions for Forced Duffing-Type Equations with Damping Term. (10th March 2011) - Li, Yongkun; Zhang, Tianwei
Abstract : Using the variational principle of Ricceri and a local mountain pass lemma, we study the existence of three distinct solutions for the following resonant Duffing-type equations with damping and perturbed termu ″ ( t ) + σ u ′ ( t ) + f ( t, u ( t ) ) + λ g ( t, u ( t ) ) = p ( t ), a.e.t ∈ [ 0, ω ], u ( 0 ) = 0 = u ( ω ) and without perturbed termu ″ ( t ) + σ u ′ ( t ) + f ( t, u ( t ) ) = p ( t ), a.e.t ∈ [ 0, ω ], u ( 0 ) = 0 = u ( ω ) .